Legal Review of Legal Consequences For Members of the Online Arisan E-Master Who Are in Default in Making Arisan Money Payments According to Civil Law: (Study of Decision Number 41/Pdt.G/2021/PN Pwd) - Yarisman Zai; Roida Nababan; Meli Hertati Gultom (International Journal of Law, Crime and Justice, 2025)
Online rotating savings groups (arisan) are a form of activity involving numerous members with the purpose of periodic fund collection. In practice, these activities often give rise to various legal issues, one of which is the breach of obligations (wanprestasi) by members in fulfilling their payment commitments. Such breaches result in legal consequences that not only harm the involved parties but also have the potential to erode public trust in online rotating savings activities. One case that serves as the focus of this research is Decision Number 41/Pdt.G/2021/PN Pwd, which addresses the issue of breach of obligations within the E-Master online rotating savings group. This study aims to analyze the legal consequences arising from breaches of obligations by members in the payment of arisan contributions under civil law. Employing a normative juridical approach and case study method, this research underscores the importance of legal certainty in resolving disputes related to online rotating savings. Furthermore, it highlights the need for more specific legal regulations governing online rotating savings activities to safeguard the rights of all involved parties.